1981
DOI: 10.1111/j.1748-1716.1981.tb06766.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of indomethacin on cerebral blood flow and oxygen consumption in the rat at normal and increased carbon dioxide tensions

Abstract: The effect of the fatty acid cyclo-oxygenase inhibitor indomethacin on cerebral blood flow (CBF) and the metabolic rate for oxygen (CMRO2) was studied in paralyzed and artificially ventilated rats. In normocapnic animals, the drug (10 mg.kg-1i.v.) reduced CBF to 50% of control without a measurable effect on CMRO2. During hypercapnia (PaCO2 70-80 mmHg) the increase in CBF was reduced by about 80% but CMRO2 remained unchanged. Autoradiographic evaluation of local CBF in 20 brain structures indicated that the red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0

Year Published

1981
1981
2006
2006

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(49 citation statements)
references
References 34 publications
5
44
0
Order By: Relevance
“…As stated, all studies have shown that indomethacin reduces CBF at constant CMR02. However, in spection of the present data, and those reported by Dahlgren et al (1981), shows that in all groups studied (normo-and hypercapnic animals), the mean value for CMR02 was lower in indomethacin treated animals. In order to test the possibility that a true decrease in CMR02 remained undetected due to the small groups studied, we calculated all individ- The second and controversial issue referred to concerns the effect of hypercapnia on CMROz.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…As stated, all studies have shown that indomethacin reduces CBF at constant CMR02. However, in spection of the present data, and those reported by Dahlgren et al (1981), shows that in all groups studied (normo-and hypercapnic animals), the mean value for CMR02 was lower in indomethacin treated animals. In order to test the possibility that a true decrease in CMR02 remained undetected due to the small groups studied, we calculated all individ- The second and controversial issue referred to concerns the effect of hypercapnia on CMROz.…”
Section: Discussionsupporting
confidence: 78%
“…A similar reduction in CO2 sensitivity has been noted in the baboon, in which chloralose anesthesia (as compared to Sernylan anesthesia) reduced both CMR02 and the CO2 responsiveness (Sandor et aL, 1977). It is clear that the CO2 responsiveness, so calculated, is reduced by indomethacin, although the drug does not decrease CMR02 significantly (Pickard and MacKenzie, 1973;Sakabe and Siesj6, 1979;Dahlgren et aL, 1981).…”
Section: Discussionsupporting
confidence: 54%
“…The blood flow decreasing effect of indomethacin lasts for at least 150 minutes in the human brain. 21 Systemic administration of indomethacin also decreases cerebral blood flow in rabbits, 1 rats, 22 newborn pigs, 23 24 and humans. 21 25 However, Cuypers et al did not find this effect in the rabbits they examined.…”
Section: Discussionmentioning
confidence: 99%
“…Previous animal studies of the effects of indomethacin on CMR O 2 gave conflicting results of no change (Dahlgren et al, 1981;Pickard and MacKenzie, 1973) or reduction (Nowicki et al, 1987). The only tomographic study on living animals (Schumann et al, 1996), found no change of the global CMR O 2 but interestingly (see below) a small and significant increase of CMR O 2 in thalamus and pons.…”
Section: Effect Of Indomethacin On Cmr Omentioning
confidence: 95%